2019
DOI: 10.13057/biodiv/d200405
|View full text |Cite
|
Sign up to set email alerts
|

The The favorable alleles of AKIRIN2:c.*188G>A, EDG1:c.-312A>G and TTN:g.231054C>T as candidate markers for high-marbling are very low in Bali cattle

Abstract: Abstract. Anwar S, Wulandari AS, Putra WPB, Said S. 2019. The favorable alleles of AKIRIN2:c.*188G>A, EDG1:c.-312A>G and TTN:g.231054C>T as candidate markers for high-marbling are very low in Bali cattle. Biodiversitas 20: 965-970. Marbling is one of primary factors influencing the palatability of beef. The AKIRIN2, EDG1 and TTN genes are considered as the three candidate genes responsible for high-marbling in beef cattle. This study aimed to investigate the genetic polymorphism of the SNPs of AKIRIN2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
2
1
0
Order By: Relevance
“…The consistent presence of the A allele in Bali cattle indicates that the breed does not have a genetic propensity for high marbling scores. This finding is consistent with previous studies and reinforces the hypothesis proposed by [22] regarding the genetic predisposition of Bali cattle for high marbling scores. The absence of favourable alleles for high marbling scores in the identified candidate genes (TG5, AKIRIN2 and EDG1) supports the notion that Bali cattle did not have favourable alleles as high marbling cattle [22,27].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The consistent presence of the A allele in Bali cattle indicates that the breed does not have a genetic propensity for high marbling scores. This finding is consistent with previous studies and reinforces the hypothesis proposed by [22] regarding the genetic predisposition of Bali cattle for high marbling scores. The absence of favourable alleles for high marbling scores in the identified candidate genes (TG5, AKIRIN2 and EDG1) supports the notion that Bali cattle did not have favourable alleles as high marbling cattle [22,27].…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with previous studies and reinforces the hypothesis proposed by [22] regarding the genetic predisposition of Bali cattle for high marbling scores. The absence of favourable alleles for high marbling scores in the identified candidate genes (TG5, AKIRIN2 and EDG1) supports the notion that Bali cattle did not have favourable alleles as high marbling cattle [22,27]. In the TG5 gene, studies on Wagyu cattle by [28] showed a higher frequency of the TT genotype associated with high marbling scores, while in Bali cattle, only the CC genotype was observed [27].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation